PERSEPSI MAHASISWA ATAS PENGARUH TEKNOLOGI INFORMASI TERHADAP KUALITAS INFORMASI AKUNTANSI DENGAN ETIKA PENGGUNA SEBAGAI VARIABEL MODERASI - Pungkasih Titi Sari; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
The aim of this study was to obtain empirical evidence on student perceptions of the effect of information technology on the quality of information. In addition, this study was also conducted to obtain empirical evidence of how influential ethics users of interaction between information technology on the result of quality of information. In this study, the data collection method used is purposive sampling with respondents criteria should be accounting student, level education S1 and S2. Esspecially for S1 which has been taking courses in Practical Accounting and Auditing Practice. This study uses Accounting students S1 and S2 Diponegoro University as a population. Of the entire population of the samples was 114 respondents. The data obtained were analyzed using the SPSS statistical analysis of descriptive technical, test data quality, classical assumption, and the absolute difference test. The results of this study indicate that information technology under ethical users has a positive effect on the result of quality of accounting information by the students.